Solar Illumination Control of the Polar Wind. Issue 11 (26th November 2017) - Maes, L.; Maggiolo, R.; De Keyser, J.; André, M.; Eriksson, A. I.; Haaland, S.; Li, K.; Poedts, S.
Abstract: Polar wind outflow is an important process through which the ionosphere supplies plasma to the magnetosphere. The main source of energy driving the polar wind is solar illumination of the ionosphere. As a result, many studies have found a relation between polar wind flux densities and solar EUV intensity, but less is known about their relation to the solar zenith angle at the ionospheric origin, certainly at higher altitudes. The low energy of the outflowing particles and spacecraft charging means it is very difficult to measure the polar wind at high altitudes. We take advantage of an alternative method that allows estimations of the polar wind flux densities far in the lobes. We analyze measurements made by the Cluster spacecraft at altitudes from 4 up to 20  R E . We observe a strong dependence on the solar zenith angle in the ion flux density and see that both the ion velocity and density exhibit a solar zenith angle dependence as well. We also find a seasonal variation of the flux density. Key Points: Polar wind flux density exhibits a dependence on the solar zenith angle Both density and velocity in the polar wind show similar but weaker solar zenith angle dependence Seasonal variations are observed in the polar wind flux density